Tech Savvy : Advancing GovTech Reforms in Public Administration - World Bank (Washington, DC, 2022)
GovTech is one strategy that governments have adopted to more effectively respond to citizen needs and improve the effectiveness and efficiency of public service delivery. Yet, all too often a government’s information and communications technology (ICT) projects do not deliver on their promise, and the public sector has a history of projects falling short of expectations, going over time and budget and taking years to deliver on their potential. There are a number of challenges that need to be overcome for GovTech solutions to work, and this report focuses on three key challenges that the World Development Report (WDR) 2016 called the analog complements, which underpin effective digital transformation in the public sector: a whole-of-government coordination, civil service digital skill development, and an innovative culture in public sector organizations. This report focuses on three key analogue complements that can get in the way of successful GovTech projects: coordination, capacity, and culture.